2003
DOI: 10.1145/636772.636776
|View full text |Cite
|
Sign up to set email alerts
|

The new productivity paradox

Abstract: ECONOMIC studies cx)nduaed in the 1980s and early 1990s failed to find evidence of improved firm productivity corresponding to greater IT investment. Because business firms expeaed performance to improve as a result of IT, the failure to observe higher productivity (more output from resources employed) was dubbed the "productivity paradox" [5]. The alleged implication was that they had overinvested in computers and other IT.If firm productivity did improve with investment in IT, the shareholder value of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 7 publications
2
43
0
Order By: Relevance
“…Closely related to these studies is the emerging literature on the value of enterprise systems, that have shown that investments in ERP Anderson et al 2003) and combinations of ERP systems with other complementary enterprise technologies such as SCM or CRM is associated with significantly greater firm value (Aral et al 2006). It has long been recognized that a key source of value of ERP systems is the ability to facilitate organizational decision making (see e.g.…”
Section: Business Value Of Information Technologymentioning
confidence: 99%
“…Closely related to these studies is the emerging literature on the value of enterprise systems, that have shown that investments in ERP Anderson et al 2003) and combinations of ERP systems with other complementary enterprise technologies such as SCM or CRM is associated with significantly greater firm value (Aral et al 2006). It has long been recognized that a key source of value of ERP systems is the ability to facilitate organizational decision making (see e.g.…”
Section: Business Value Of Information Technologymentioning
confidence: 99%
“…They also show that, among adopters, performance increases when ERP is implemented. Anderson et al (2003) find a large stock market valuation multiple from ERP investments. These studies demonstrate that the benefits of ERP systems are positive on average when we look at aggregated, firm-level performance.…”
Section: Enterprise Resource Planning (Erp) Systemsmentioning
confidence: 99%
“…Regarding the second question, a majority of mid-size and Fortune 500 companies have turned to enterprise resource planning (ERP) systems (also known as enterprise systems) as a means of increasing integration among business functions (Scott and Shepherd, 2002;META Group, 2004). In spite of early evidence to the contrary, ERP systems do appear to yield benefits to the average firm (Hitt, Wu and Zhou, 2002;Anderson, Banker and Ravindran, 2003). However, how and where these benefits occur (and do not occur) within a company has not been as thoroughly researched.…”
Section: Introductionmentioning
confidence: 99%
“…For example, enterprise resource planning (ERP) systems, which have been available in the market since mid 1980s, have not been widely adopted for about a decade. Most companies had adopted a wait-and-see strategy until they faced the Y2K problem in their legacy systems in mid 1990s [1], [34] [40]. In the conclusion section of this paper, we will discuss why our models can help managers better understand the two drastically different investment strategies used in the two cases.…”
Section: Introductionmentioning
confidence: 99%